In situ construction of ossification micro-units for critical bone regeneration via sustained lifting of epigenetic suppression - Yang, Wu; Ding, Tao; Zhuang, Pengzhen; Chen, Yu; Zhang, Yu; Chen, Zehao; Fan, Minjie; Viitala, Tapani; Wang, Zhongmin; Cui, Wenguo; Zhang, Hongbo (Elsevier, 2025)
Critical-sized bone defects present significant clinical challenges due to insufficient stem cell recruitment, epigenetic suppression of osteogenesis, and inadequate mineralization. Among the epigenetic suppression mechanisms, upregulated MEG3 specifically recruits the epigenetic regulator EZH2 to block the transcription of β-catenin, a core gene for bone regeneration. To regulate MEG3 in vivo effectively, we used microfluidics to develop in situ continuous MEG3-silencing ossification micro-units (MSOMs) that integrate “material–gene–biofactor” tri-coupling into a unified biomaterial system. The MSOMs are nano-micro particles composed of amorphous calcium phosphate nanoparticles loaded with siRNA (si@BCP) in GelMA microgels loaded with stromal cell-derived factor-1α (SDF-1α). The SDF-1α in the microgel layer is rapidly released to recruit BMSCs, while the siRNA in si@BCP has sustained release to silence MEG3 and restore β-catenin transcription continuously. Thus, the MSOMs provide a stable mineralization microenvironment for ossification center formation. In vivo observations revealed the formation of ossification centers around these micro-units, tripling new bone formation and achieving efficient bone regeneration. By addressing the key limitations of traditional therapies, MSOMs offer a clinically viable solution that integrates stem cell recruitment, epigenetic regulation, and biomaterial-based mineralization, thus providing a highly efficient approach for critical bone defect repair.